Pemberdayaan UMKM Lokal Melalui Integrasi Website Desa sebagai Media Pemasaran Digital di Desa Pentadu Barat: Empowering Local MSME through the Integration of Village Website as a Digital Marketing Platform in Pentadu Barat Village - Kartika, Dhian Satria Yudha; Sukma, Dini Artika; Lasarudin, Alter; Luawo, Salma Rivani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The development of digital technology has created new opportunities for Micro, Small, and Medium Enterprises (MSMEs) to expand their market reach. However, in Pentadu Barat Village, MSME product promotion had previously relied on conventional methods, limiting the potential for local economic growth. Through the Community Service Program (KKN), MSMEs were integrated into the official village website, which features village profiles, MSME catalogs, articles and galleries, testimonials, and contact services. This study aims to describe the integration process and assess the role of the village website as a digital promotional medium. The research employed a qualitative descriptive approach, involving observation, data collection on business identity, and interviews with MSME actors and village officials. The findings indicate that the village website serves as an effective promotional medium, as reflected in increased visibility of local products, more structured digital documentation, and positive community responses. Nevertheless, the main challenge lies in sustainability, particularly regarding data updates and content management. With consistent management, the village website can function not only as a digital showcase but also as an instrument of community empowerment and local economic strengthening in the digital era.